2(m-1)-4(m+2)=24

Simple and best practice solution for 2(m-1)-4(m+2)=24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(m-1)-4(m+2)=24 equation:


Simplifying
2(m + -1) + -4(m + 2) = 24

Reorder the terms:
2(-1 + m) + -4(m + 2) = 24
(-1 * 2 + m * 2) + -4(m + 2) = 24
(-2 + 2m) + -4(m + 2) = 24

Reorder the terms:
-2 + 2m + -4(2 + m) = 24
-2 + 2m + (2 * -4 + m * -4) = 24
-2 + 2m + (-8 + -4m) = 24

Reorder the terms:
-2 + -8 + 2m + -4m = 24

Combine like terms: -2 + -8 = -10
-10 + 2m + -4m = 24

Combine like terms: 2m + -4m = -2m
-10 + -2m = 24

Solving
-10 + -2m = 24

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + -2m = 24 + 10

Combine like terms: -10 + 10 = 0
0 + -2m = 24 + 10
-2m = 24 + 10

Combine like terms: 24 + 10 = 34
-2m = 34

Divide each side by '-2'.
m = -17

Simplifying
m = -17

See similar equations:

| 3.1p+29=4.1p-14 | | (3v+7)(2+v)=0 | | X-2(-1)+2=0 | | 2p^6y+1=16p^4 | | 0.01(x-4)=100 | | (5y+.4)=11.9 | | X=2y-50 | | 25=10(X-5) | | 2+5+-3=24 | | 2(m-3)=4 | | -1.2+3.618= | | 86+2(3x-12)=180 | | 1-2y+2=0 | | 120x-(5000-0.75x)= | | (x-1)(x-3)(x-5)(x-7)=20 | | (X-8)33=180 | | 8+n*2n=72 | | 5.4-0.103= | | 2k=p+2v | | 4x=18.8 | | 12*x=-3 | | 6x+3500=4x+4000 | | 86+2(3x-12)= | | 3(2x+1)x=-39 | | 8.3-(-2.1)= | | 5=q+12 | | 9x^3+6x^3+7= | | 120(5000-0.75x)= | | y=-16t^2+64t+8 | | .02y+.18=3 | | 0+4+4x= | | (3x-20)+(2x)=180 |

Equations solver categories